2022
DOI: 10.3390/ani12131605
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Modifications in Spermatogenesis during Seasonal Testicular Regression: An Update Review in Mammals

Abstract: Testicular regression occurs during the non-breeding season in many mammals. This affects spermatogenesis, resulting in decreased or arrested activity. Both lead to a decrease or cessation in sperm production. In recent years, the cellular mechanisms that lead to infertility in males in non-reproductive periods have been studied in very different species of mammals. At the start of the present century, the main mechanism involved was considered as an increase in the apoptotic activity of germ cells during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 86 publications
(127 reference statements)
0
2
0
Order By: Relevance
“…However, this increase is only subtle, at a rate that possible does not explain the rapid total testicular regression of this species. Thus, based on our results, we agree with Beltrán‐Frutos et al (2022) in postulating that there are possibly several different mechanisms that participate separately or jointly in each species (in a specie‐specific manner) to perform/regulate the process of testicular regression.…”
Section: Discussionsupporting
confidence: 92%
“…However, this increase is only subtle, at a rate that possible does not explain the rapid total testicular regression of this species. Thus, based on our results, we agree with Beltrán‐Frutos et al (2022) in postulating that there are possibly several different mechanisms that participate separately or jointly in each species (in a specie‐specific manner) to perform/regulate the process of testicular regression.…”
Section: Discussionsupporting
confidence: 92%
“…They exhibit permeation of the blood–testis barrier, lower testosterone production, complete arrest of spermatogenesis, and inhibited mating behavior. Previous studies have indicated that the cellular mechanism of testicular regression is related to apoptosis in both germ cells and Sertoli cells, as well as a decrease in the number of Leydig cells ( Morales et al, 2002 ; Islam et al, 2012 ; Jiménez et al, 2015 ; Beltrán-Frutos et al, 2022 ; Valentini, et al, 2022 ). In recent years, the underlying mechanisms involved in testicular regression and loss of fertility in males have been well-studied in mammals ( Sharma et al, 2019 ; Wang et al, 2019 ; Tabecka-Lonczynska et al, 2020 ; Wang et al, 2021 ; Yao et al, 2023a ; Yao et al, 2023b ).…”
Section: Discussionmentioning
confidence: 99%
“…In seasonal breeders, male plasma T levels typically exhibit a pronounced peak during the breeding season, play a pivotal role in the development of male genitalia, support sperm production, and regulate mating behavior ( Shi et al, 2007a ). These alterations culminate in a decline in fertility and inhibited mating behavior ( Jiménez, et al, 2015 ; Zhu et al, 2017 ; Beltrán-Frutos, et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The spermatogenic tubules that comprise the testes of higher vertebrates (amniotes; reptiles, birds and mammals) aptly display the essence of this indispensableness with the Sertoli cells constituting a permanent cellular backbone of the tubular wall during which successive germ cell cohorts are layered from base to lumen in the cytoplasmic folds of the Sertoli cells (Franca et al., 2016; Yoshida, 2016). The very first report of a rare instance of Sertoli cell death, namely that occurring in a bird species, the European Starling (Young et al., 2001), not surprisingly elicited much debate about the broader implications of the loss of this anchoring cell in the amniote seminiferous epithelium (Beltrán‐Frutos et al., 2022). Subsequent reports of similar deaths in other amniote species (Islam et al., 2012; Jenkins et al., 2007; Martínez‐Hernández et al., 2020; Seco‐Rovira et al., 2014) prompted the latter review to conclude that the Sertoli cell kinetics of vertebrates are probably far more dynamic than previously thought (Beltrán‐Frutos et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The very first report of a rare instance of Sertoli cell death, namely that occurring in a bird species, the European Starling (Young et al., 2001), not surprisingly elicited much debate about the broader implications of the loss of this anchoring cell in the amniote seminiferous epithelium (Beltrán‐Frutos et al., 2022). Subsequent reports of similar deaths in other amniote species (Islam et al., 2012; Jenkins et al., 2007; Martínez‐Hernández et al., 2020; Seco‐Rovira et al., 2014) prompted the latter review to conclude that the Sertoli cell kinetics of vertebrates are probably far more dynamic than previously thought (Beltrán‐Frutos et al., 2022). The extent and mechanisms of these Sertoli deaths, not to mention the disposal of the corpses of these large‐bodied cells, have eluded systematic research inquiry, in part, due to the swiftness of mammalian cell kinetics to maintain tissue integrity and the complex organization of the amniote testis.…”
Section: Introductionmentioning
confidence: 99%